1983
DOI: 10.1002/cne.902190309
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in retinal ganglion cell and optic axon populations in the pigmented rat

Abstract: The number of ganglion cells in the retina of the postnatal rat has been examined. We estimated both the number of axons in the optic nerve and the number of cells which can be retrogradely labelled with horseradish peroxidase from injections into the brain. In the retina of the newborn rat there are at least twice as many ganglion cells as in the adult rat. By retrograde labelling of the ganglion cells and following transection of their axons 24-48 hrs later we can find no evidence that ganglion cells withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
218
4
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(250 citation statements)
references
References 43 publications
24
218
4
4
Order By: Relevance
“…Therefore, we examined the number of CASP3ϩ cells in control and mutant retinas. Previous research has shown that apoptosis is rare throughout embryogenesis (35,36). We found no significant change of the number of apoptotic cells at E12.5 in both control and mutant retinas (data not shown).…”
Section: -Dј E-eј F-fј)supporting
confidence: 42%
“…Therefore, we examined the number of CASP3ϩ cells in control and mutant retinas. Previous research has shown that apoptosis is rare throughout embryogenesis (35,36). We found no significant change of the number of apoptotic cells at E12.5 in both control and mutant retinas (data not shown).…”
Section: -Dј E-eј F-fј)supporting
confidence: 42%
“…Retinal areas were measured with a computer-assisted image analyzer. Pyknotic cells were identified in the ganglion cell layer by the presence of condensed and darkly stained nuclei, sometimes fragmented in separated bodies, as described by Perry et al, 1983. When two or more clumps were observed within a cell diameter, they were counted as one pyknotic cell.…”
Section: Methodsmentioning
confidence: 99%
“…In the rat, ∼50% of the total RGC population dies in the first postnatal week soon after reaching their target axons, the SC, and the dLGN (Perry et al 1983). While BDNF or NT-4/5 injected into the SC promotes the survival of neonatal RGCs (Cui and Harvey 1995;Ma et al 1998), BDNF or NT-4/5 mutant mice have normal RGC numbers and double-mutant mice show delay in the inner retinal development (Cellerino et al 1997;Harada et al 2005).…”
Section: The Neural Retinamentioning
confidence: 99%
“…Proliferation of retinal progenitors may also be partly controlled by extrinsic cues such as ciliary neurotrophic factor (CNTF), bone morphogenetic protein (BMP), and fibroblast growth factor (FGF) molecules; however, these effects appear independent of fate and differentiation cues among both early and late progenitor cells (Cepko 1999;Yang 2004). During development, nearly half of RGCs experience programmed cell death (PCD) (Perry et al 1983). Many transcription factors, neurotrophic factors, cell deathregulating factors, and caspases have all been implicated in the regulation of developmental RGC death (Isenmann et al 2003).…”
Section: The Neural Retinamentioning
confidence: 99%